Forced Displacement: Legal Versus Illegal Crops (2012)
Anecdotal evidence suggests that, in stateless regions in Colombia, the establishment of oil palm 1 plantations generates more forced migration than the introduction of coca crops. We provide a theoretical model to study this phenomenon where an agent, allied with the illegal armed group that controls a region, chooses between buying an agricultural good from peasants or producing it himself by evicting farmers from their lands. We compare two crops that differ in their labor intensity. Results indicate that it is more likely that the agent finds it optimal to displace peasants in the case of the less labor intensive crop. © 2012 Copyright Taylor and Francis Group, LLC.